2020
DOI: 10.21873/invivo.12063
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ascorbic Acid and U-74389G on Renal Ischemia-Reperfusion Injury in a Rat Model

Abstract: Background/Aim: U-74389G and ascorbic acid protect the cells from oxidation. This study aimed to depict their role in ischemia-reperfusion injury in a renal rat model. Materials and Methods: Sixty Wistars rats were randomized into six groups of 10 animals each. Group A Ischemia 30 min, reperfusion 60 min; Group B Ischemia 30 min, reperfusion 120 min; Group C Ischemia 30 min, ascorbic acid administration, reperfusion 60 min; Group D Ischemia 30 min, ascorbic acid administration, reperfusion 120 min; Group E Isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…[9,22,25] Many recent studies have shown that both histopatholog-ical changes occur in RIRI and these changes are reduced by various agents. [16,26,27] This study revealed that similar to previous studies, oxerutin pretreatment significantly relieved the severity of histopathological changes. To our knowledge, apoptosis, one of the important mechanisms of cell death, is an important prognostic factor in the development of ARF induced by I/R injury.…”
Section: Güzel Et Al the Efficiency Of Oxerutin On Apoptosis And Kidn...supporting
confidence: 90%
See 2 more Smart Citations
“…[9,22,25] Many recent studies have shown that both histopatholog-ical changes occur in RIRI and these changes are reduced by various agents. [16,26,27] This study revealed that similar to previous studies, oxerutin pretreatment significantly relieved the severity of histopathological changes. To our knowledge, apoptosis, one of the important mechanisms of cell death, is an important prognostic factor in the development of ARF induced by I/R injury.…”
Section: Güzel Et Al the Efficiency Of Oxerutin On Apoptosis And Kidn...supporting
confidence: 90%
“…[13][14][15] However, reperfusion times ranging from 1 h to 24 h were evaluated in the studies. [13][14][15][16] Since we considered that the improvement of early-stage RIRI will be a positive recovery sign for the late-stage renal functions, we conducted our RIRI model in such a way that 30 min of ischemia followed by 1 h of reperfusion. In the histopathological examinations and apoptotic index evaluations, the kidney tissues in the sham control group had a normal histopathological appearance and low apoptotic index, but those in the RIRI and RIRI + oxerutin groups exhibited deteriorated histopathological structure and apoptotic index at varying levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Vitamin C has already been studied for limiting the effects of RHR injury in both animal models and in vitro studies. 39 In contrast, the role of retinol in countering RHR injury has not been studied to date. Therefore, this study aimed to evaluate the influence of both antioxidant vitamins and their combinational dose for preventing RHR injury.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Antioxidant vitamins in high doses neutralize the negative effects of the oxidative bursts during reperfusion by either neutralizing the effect of ROS or by preventing the bursts from occurring . Vitamin C has already been studied for limiting the effects of RHR injury in both animal models and in vitro studies . In contrast, the role of retinol in countering RHR injury has not been studied to date.…”
Section: Resultsmentioning
confidence: 99%